Organizational culture, power distance and corruption: The mediating role of religiosity - Maulidi, Ach; Wisnu Girindratama, Muhammad; Soeherman, Bonnie; Arastyo Andono, Fidelis (The Indonesian Accounting Review, 2024)
We examine how organizational culture and power distance influence religiosity and, in turn, how these variables affect corruption. We gathered data from Indonesian public servants and analyzed the relationships using PLS-SEM. The findings suggest a significant inverse relationship between religiosity and corruption, reinforcing ethical paradigms that position religious adherence as a key deterrent to corrupt behavior. Notably, religiosity acts as a critical mediator, negatively channeling the effects of organizational culture on corruption. However, this mediating effect does not extend to the power distance-corruption nexus, suggesting that the hierarchical structure may not inherently bear upon moral conduct. Interestingly, while organizational culture positively shapes religiosity, power distance does not exhibit a similar influence, highlighting the complex roles these organizational variables play in shaping ethical behavior. Theoretically, the findings challenge assumptions about the direct ethical impact of hierarchical structures, adding depth to existing frameworks onpower distance and moral conduct. For policymakers and organizational leaders, the findings underline the importance of fostering a culture that promotes religiosity as a deterrent to corruption.